1995
DOI: 10.1152/ajpgi.1995.269.3.g418
|View full text |Cite
|
Sign up to set email alerts
|

Gastrokinetic effects of erythromycin: myogenic and neurogenic mechanisms of action in rabbit stomach

Abstract: The aims of this study were to determine regional differences and the mechanism of gastric contractile effects of erythromycin. Rabbit gastric circular muscle strips were studied in vitro. The threshold dose for erythromycin was significantly less and the maximum contraction greater in the antrum (1 microM and 0.9 +/- 0.3 kg/cm2) than in the fundus (10 microM and 0.3 +/- 0.1 kg/cm2). Erythromycin-induced antral contractions were decreased by motilin tachyphylaxis but unaffected by tetrodotoxin, atropine, hexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 0 publications
5
45
0
4
Order By: Relevance
“…3,10 There is substantial evidence to support the suggestion that erythromycin exerts its gastrointestinal motor effects through activation of the neural motilin receptors on cholinergic neurons and the smooth muscle motilin receptors of the upper gastrointestinal tract. 11 Stimulation of the motilin pathway results in greater amplitude and more frequent antral 14 and suppression of pyloric pressure waves, which is associated with reduced pyloric outlet resistance and an increase in duodenal contraction frequency. 15 Combination of the aforementioned mechanisms is thus likely to produce powerful propulsive forces which effectively propel the gastric luminal contents distally towards the small and large bowels and improve gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 99%
“…3,10 There is substantial evidence to support the suggestion that erythromycin exerts its gastrointestinal motor effects through activation of the neural motilin receptors on cholinergic neurons and the smooth muscle motilin receptors of the upper gastrointestinal tract. 11 Stimulation of the motilin pathway results in greater amplitude and more frequent antral 14 and suppression of pyloric pressure waves, which is associated with reduced pyloric outlet resistance and an increase in duodenal contraction frequency. 15 Combination of the aforementioned mechanisms is thus likely to produce powerful propulsive forces which effectively propel the gastric luminal contents distally towards the small and large bowels and improve gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that its prokinetic action is mediated via the motilin pathway [23][24][25] and results in increasing proximal gastric tone [26] , enhancing the strength and frequency of antral and proximal small bowel contractions [27][28][29][30][31] and reducing pyloric outlet resistance [24] . More importantly, recent studies have discovered 2 main types of motilin receptors [32] . The neural motilin receptor on cholingeric neurons is principally stimulated by low dose (1-3 mg/kg) erythromycin and can augment phase III migrating motor complexes, whilst the smooth muscle motilin receptor responds to higher doses and produces sustained antral contractions and promotes antroduodenal coordination [25,30,33,34] .…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Numerous studies have demonstrated the presence of motilin receptors on smooth muscle cells, which appear to facilitate or augment nerve-mediated effects of motilin (4,6,18,27,28,34). Radioligand binding studies on gastric and intestinal membranes enriched with smooth muscle markers (5Ј-nucleotidase) provide evidence for the presence of motilin receptors on smooth muscle cells (3,8,36).…”
mentioning
confidence: 99%